Study on the canning of heart-of-pal (Euterpe edulis Mart.): III. influence of pretreatment solutions and processing times - Nogueira, João N.; Fonseca, Homero (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1982)
The objective of this paper was to study the influence of pretreatment solutions and processing times on the quality of canned heart-of-palm (Euterpe edulis Mart.). The results showed that, in general, the best processing method was the pretreatment solution 5% NaCl + 1% k2s2o5 combined with thermal processing times of 50 minutes for the first three cuts and 60 minutes for the last ones. For the first three cuts, in particular, the pretreatment solution 5% NaCl + 1% citric acid combined with 45 minutes of thermal processing presented the best results for all attributes of quality, except for flavor, in which the pretreatment solution 1% citric acid + 0,25% ascorbic acid with 40 minutes of thermal processing was superior.